That's writing talk: An insight into the Academic Writing Readers Group - Rebecca Bell (Association for Learning Development in Higher Education (ALDinHE), 2010)
Despite being comprised of 'academic communities' Higher Education often provides academics from different disciplines with few opportunities to discuss common practices or concerns.. Some issues, such as student writing, are so widespread, that there is however a need for staff to have the opportunity to work collaboratively. A focused community or network provides staff with the opportunity to share good practice and develop new ideas. Such a group has been established at Nottingham Trent University to explore the issue of student writing. This article examines the 'Academic Writing Readers Group' and discusses the challenges and benefits of using a community of practice approach to the issue of student writing.